La Forteresse sous la maison : la tentative de normalisation de l’entreprise coloniale israélienne en territoires palestiniens occupés - Clarisse Genton (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2025)
The Israeli colonial enterprise began in a context of military occupation at the end of the Six-Day War in 1967. For the last fifty-seven years, the Israeli state has been building residential communities in East Jerusalem and the West Bank for the exclusive use of its citizens, encroaching on the occupied Palestinian territories. This article looks at the coloniality of architecture by analyzing the housing units built for this purpose, with a particular focus on a unique type of building that appeared in the early 1990s, at a turning point in the history of the conflict. Over the last three decades, this typology has spread throughout the occupied territories. It exemplifies a series of phenomena directly linked to the context in which it emerged, and at the same time tells us about the contradictions of the colonizer.